Les chanteuses haïtiennes à Montréal: des témoins d’une culture - Amédée, Alourdes (Ethnologies, 1993)
In Haiti, songs, widely sung by women, accompany almost every gesture of daily life, especially those related to domestic activities. This paper presents the results of research carried out on Haitian women living in Montreal. What types of songs do they sing in a culture not their own? Is there a modification of their traditional repertoire or does it remain the same? What social functions do these songs have in their original culture and in their culture of adoption? Are songs passed on to the next generation born in Montreal and, if so, how are they transmitted? This study will attempt to answer these questions.